Determination of the size of the dust torus in H0507+164 through optical and infrared monitoring. Issue 4 (29th January 2018) - Mandal, Amit Kumar; Rakshit, Suvendu; Kurian, Kshama S; Stalin, C S; Mathew, Blesson; Hoenig, Sebastian; Gandhi, Poshak; Sagar, Ram; Pandge, M B
Abstract: The time delay between flux variations in different wavelength bands can be used to probe the inner regions of active galactic nuclei (AGNs). Here, we present the first measurements of the time delay between optical and near-infrared (NIR) flux variations in H0507+164, a nearby Seyfert 1.5 galaxy at z = 0.018. The observations in the optical V -band and NIR J, H, and K s bands carried over 35 epochs during the period 2016 October to 2017 April were used to estimate the inner radius of the dusty torus. From a careful reduction and analysis of the data using cross-correlation techniques, we found delayed responses of the J, H, and K s light curves to the V -band light curve. In the rest frame of the source, the lags between optical and NIR bands are found to be 27.1^+13.5_-12.0 d ( V versus J ), 30.4^+13.9_-12.0 d ( V versus H ) and 34.6^+12.1_-9.6 d ( V versus K s ). The lags between the optical and different NIR bands are thus consistent with each other. The measured lags indicate that the inner edge of dust torus is located at a distance of 0.029 pc from the central ultraviolet/optical AGN continuum. This is larger than the radius of the broad line region of this object determined from spectroscopic monitoring observations thereby supporting the unification model of AGN. The location of H0507+164 in the τ– M V plane indicates that our results are in excellent agreement with the now known lag-luminosity scaling relationship for dust in AGN.